Review Paper on the Level of Road Surface Damage in Mataram City - Fatikasari, Aulia Dewi; Aryaseta, Bagas; Alfiansyah, Achmad Dzulfiqar (UPN Veteran Jatim, 2024)
In Mataram City, the capital of West Nusa Tenggara Province, many road sections have deteriorated, reducing road comfort, safety, and mobility efficiency. Typical forms of road damage, such as cracks, potholes, deformation, and surface wear, demand regular maintenance and repairs to extend road service life. This situation underscores the need for a thorough mapping of road pavement damage to provide a comprehensive overview of the road network’s condition and to support effective maintenance planning. The mapping of pavement damage in Mataram City is also expected to inform more effective decision-making in road management. This study aims to review previous research on pavement damage mapping and apply the findings to road sections in Mataram City. This empirical, data-driven approach is anticipated to provide a thorough perspective on pavement conditions and serve as a foundation for the local government’s efforts to create more effective and efficient road maintenance policies. This study employs a systematic literature review approach to analyze and synthesize existing research regarding pavement damage in road sections using the PCI and Binamarga Methods on Mataram City roads. This study is classified as qualitative research, focused on extracting and synthesizing information from academic papers. Based on the research results from several journal reviews, in the city of Mataram,, several roads still experience visual damage to the pavement surface, including cracking, depression, patching and utility cut patching, and potholes. In addition, the results show that several roads experience fair-level damage based on the PCI method, and some have less than 50% damage to the road surface based on the Binamarga method